Disempowered Mothers Have Undernourished Children: How Strong Is the Intrinsic Agency? - Poudel, Sujan; Adhikari, Chiranjivi; Yadav, Rajesh Kumar; Yadav, Dipendra Kumar; Thapa, Deependra Kaji; Jakovljevic, Mihajlo (Frontiers in Public Health, 2022)
Objective Undernutrition is one of the leading causes of morbidity and mortality among under-five children, particularly in low-and-middle-income countries. Since women, including mothers, are the primary caregivers of their children, their empowerment status can inherently influence children's nutritional status. Empowerment is, mainly, an intrinsic agency developed as an affective domain trajectory or attitude that guides the skill or behavior. This study aimed to assess the association between women's empowerment and nutritional status of their children. Methods A cross-sectional study was carried out among 300 mothers having children aged 6–59 month in rural municipalities of Kaski district in Nepal. Face to face interview and various anthropometric measurements were used to collect data. Chi-square test was performed to assess the association between women's empowerment and children's nutritional status, and multivariable logistic regression was used to assess the strength of association. Results Of 300 mothers having 6–59 months' children, nearly half (49%) were highly empowered while around 38% children were in poor nutritional status. More than one-fourth (26.7%) children were stunted, 7% were wasted, 17.7% were underweight, and in overall, nearly 38% were in poor nutrition. There was a five-fold increase in odds of wasting, thirty-fold increase in odds of stunting, and twenty-nine-fold increase in odds of underweight among children whose mothers had low empowerment status compared to their counterparts. Conclusion Overall, this study exhibited that maternal empowerment strongly affected children's nutritional status, especially stunting and underweight. Thus, intrinsic factor, mainly education and community membership are suggested to empower them for making their own decisions. Interventions aiming to improve nutritional status of children should include women empowerment incorporating dimensions of material resources. Further empirical evidence is required from trials and cohort studies.